2013
DOI: 10.1111/1744-9987.12143
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine and Albumin Decline Predict the Contraction of Nosocomial Aspiration Pneumonia in Patients Undergoing Hemodialysis

Abstract: Aspiration pneumonia (AP) is prevalent in older adults and the hemodialysis (HD) population has been getting older. Therefore, it is speculated that increasing number of HD patients would suffer from AP. However, the clinical aspects of AP in HD patients have not been elucidated. Consecutive HD patients with nosocomial AP hospitalized in our university hospital from April 2007 to December 2008 were recruited. Their clinical characteristics, risk factors for contraction, and the fatality of AP and treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Several studies have demonstrated that Scr is strongly correlated with SMM, and that low Scr is independently associated with adverse outcomes . In particular, low Scr is associated with increased mortality in patients undergoing chronic dialysis . A large retrospective study found that a low baseline Scr level is associated with increased in‐hospital mortality in critically ill patients .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that Scr is strongly correlated with SMM, and that low Scr is independently associated with adverse outcomes . In particular, low Scr is associated with increased mortality in patients undergoing chronic dialysis . A large retrospective study found that a low baseline Scr level is associated with increased in‐hospital mortality in critically ill patients .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study found a 24% reduction in infection-related death in patients with sLPD treatment. For decades, infection- and sepsis-related hospitalization and death in patients on permanent dialysis were considered a landmark of severe PEW [ 55 , 56 ]. Furthermore, the PEW inducing infection and death may be a complication that should mostly be of concern regarding patients who are on an LPD and are transitioning from CKD to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a low serum Cr level has been demonstrated as an independent risk factor in vancomycin-resistant enterococcal colonization [ 43 ] and nosocomial aspiration pneumonia [ 44 ] in HD patients. The decrease of serum Cr levels during the first 2 weeks is a risk factor of pneumonia-related mortality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a low serum Cr level has been demonstrated as an independent risk factor in vancomycin-resistant enterococcal colonization [ 43 ] and nosocomial aspiration pneumonia [ 44 ] in HD patients. The decrease of serum Cr levels during the first 2 weeks is a risk factor of pneumonia-related mortality [ 44 ]. Since swallowing and chewing are closely correlated with systemic loss of skeletal muscle mass volume [ 38 ], decreased serum Cr level may be associated with sarcopenic dysphagia, an important cause of recurrent aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%